ROBO2 is a stroma suppressor gene in the pancreas and acts via TGF-β signalling. Issue 1 (December 2018) - Pinho, Andreia; Bulck, Mathias; Chantrill, Lorraine; Arshi, Mehreen; Sklyarova, Tatyana; Herrmann, David; Vennin, Claire; Gallego-Ortega, David; Mawson, Amanda; Giry-Laterriere, Marc; Magenau, Astrid; Leuckx, Gunther; et al.
Abstract Whereas genomic aberrations in the SLIT-ROBO pathway are frequent in pancreatic ductal adenocarcinoma (PDAC), their function in the pancreas is unclear. Here we report that in pancreatitis and PDAC mouse models, epithelial Robo2 expression is lost while Robo1 expression becomes most prominent in the stroma. Cell cultures of mice with loss of epithelial Robo2 (Pdx1Cre ;Robo2F/F ) show increased activation of Robo1+ myofibroblasts and induction of TGF-β and Wnt pathways. During pancreatitis, Pdx1Cre ;Robo2F/F mice present enhanced myofibroblast activation, collagen crosslinking, T-cell infiltration and tumorigenic immune markers. The TGF-β inhibitor galunisertib suppresses these effects. In PDAC patients, ROBO2 expression is overall low while ROBO1 is variably expressed in epithelium and high in stroma. ROBO2low ;ROBO1high patients present the poorest survival. In conclusion, Robo2 acts non-autonomously as a stroma suppressor gene by restraining myofibroblast activation and T-cell infiltration. ROBO1/2 expression in PDAC patients may guide therapy with TGF-β inhibitors or other stroma /immune modulating agents. SLIT-ROBO alterations arise in pancreatic ductal adenocarcinoma (PDAC), but their role in the pancreas is unclear. Here, the authors use mouse models to show that loss of epithelial Robo2 activates the neighbouring stroma via TGF-β signalling; findings  are relevant to PDAC patients, where ROBO expression correlates with survival outcomes.